2018
DOI: 10.3390/sports6040146
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Fitness Adaptations after Eight Weeks of High-Intensity Functional Training in Physically Inactive Adults

Abstract: The purpose of this study was to characterize high-intensity functional training (HIFT) in physically inactive adults. Four men and 10 women who were inexperienced with HIFT and not performing regular physical activity performed HIFT 3 days/week for 8 weeks. Health and fitness measures were assessed before and after the intervention. Resting heart rate (73 ± 12 vs. 68 ± 11 bpm) and resting diastolic blood pressure (71 ± 7 vs. 65 ± 6 mmHg) were reduced, while resting systolic blood pressure remained unchanged. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 39 publications
9
39
2
1
Order By: Relevance
“…The mean HR for 20 min was above 93% of HRmax, and significantly higher in the high intensity treadmill training. This HR response meets the intensity recommendations from ACSM to improve cardiorespiratory fitness [15] and previous research reported modest improvements in aerobic fitness after some weeks of high-intensity functional training [16,17]. Although CrossFit ® includes a dynamic of movements with elevated repetitions and high intensity, training protocols have distinct duration, from shorter protocols of only some minutes (2 to 8 min) to longer sessions (20 to 30 min), which may directly affect cardiovascular, metabolic, and rating of perceived exertion responses.…”
Section: Introductionsupporting
confidence: 78%
“…The mean HR for 20 min was above 93% of HRmax, and significantly higher in the high intensity treadmill training. This HR response meets the intensity recommendations from ACSM to improve cardiorespiratory fitness [15] and previous research reported modest improvements in aerobic fitness after some weeks of high-intensity functional training [16,17]. Although CrossFit ® includes a dynamic of movements with elevated repetitions and high intensity, training protocols have distinct duration, from shorter protocols of only some minutes (2 to 8 min) to longer sessions (20 to 30 min), which may directly affect cardiovascular, metabolic, and rating of perceived exertion responses.…”
Section: Introductionsupporting
confidence: 78%
“…This time-dependent data on the improvement of biological parameters can evolve especially when taking into consideration nature, duration, and intensity. Several studies have reported the benefits of regular physical and sports activities for times of 12 weeks or less (Brisebois et al, 2018;Murawska-Cialowicz et al, 2015;Park et al, 2019;Posnakidis et al, 2020;Sun et al, 2019). These studies, which are mostly Caucasian, use a high-intensity functional training (HIFT) program.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning blood pressure parameters, men's SBP decreased after 12 weeks of training. Reductions in blood pressure are generally reported in longitudinal studies on the benefits of physical and sports activities in hypertensive, normotensive, overweight, and normal-weight individuals (Brisebois et al, 2018;Whelton et al, 2002). A study of the longitudinal effects of "high-intensity functional training" showed a significant reduction in diastolic blood pressure (DBP) in men, while there was no change in the PAS in both men and women (Brisebois et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional-Fitness has been increasingly growing in popularity as it is considered a more enjoyable form of exercise when compared with traditional aerobic and resistance training [17]. In addition, it is done in a shorter period of time inducing similar positive outcomes reported in strength [18], performance [19] and body composition [20] compared to longer duration more traditional type resistance and aerobic type workouts. To the best of our knowledge, this is the first study designed to examine RPE as a viable tool for controlling the intensity of a metabolic training session in trained men.…”
Section: Correlations Between Rpe and Physiological Variablesmentioning
confidence: 99%